Hepatocellular carcinoma treated with radical resection after endoscopic diagnosis of the extent of bile duct invasion: A case report - Yudai Sato; Tomoko Tadokoro; Hiroki Yamana; Hiraki Akai; Kei Takuma; Naoki Fujita; Mai Nakahara; Kyoko Oura; Koji Fujita; Joji Tani; Hideki Kamada; Asahiro Morishita; et al. (DEN Open, 2024)
Abstract Hepatocellular carcinoma invasion of the bile duct is rare and has a poor prognosis. A 77‐year‐old man presented at the emergency department with persistent pain in the right hypochondrium. Blood tests and imaging studies revealed a 70‐mm occupying lesion in the right lobe of the liver and dilated intrahepatic bile ducts. He was diagnosed with obstructive jaundice and cholangitis. Imaging studies showed an internal mass with poor contrast effects. A liver biopsy was performed to confirm the diagnosis and hepatocellular carcinoma was suspected. Endoscopic retrograde cholangiopancreatography, endoscopic ultrasound, and peroral cholangioscopy were performed to determine the treatment strategy. The bile duct invasion did not extend to the porta hepatis; therefore, right hepatic lobectomy and radical resection were performed. Bile duct invasion in hepatocellular carcinoma is rare and often difficult to diagnose by computed tomography or conventional endoscopic retrograde cholangiopancreatography. However, endoscopic ultrasound and peroral cholangioscopy enable safe and accurate diagnosis of the extent of invasion.